Textbooks Based a Culturally Responsive Teaching Approach for IPAS Learning of Elementary School - Azizah Thalib; Nuraini; Sinta Satria Dewi Pendit; Sisriawan Lapasere; Roberto Rolly Bolalong; Sri Wahyuni; Rosnadi (Mimbar Ilmu, 2026)
The limited availability of instructional resources that integrate local culture, language, and students’ experiences in science and social studies (IPAS) has made it difficult for teachers to implement the Culturally Responsive Teaching (CRT) approach, despite its significant potential to enhance learning quality. This study aims to develop and examine the feasibility, practicality, and effectiveness of a CRT-based textbook (BUDIPAS) in improving students’ learning outcomes. This research employs a development design using the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The research subjects include material experts, media experts, cultural experts, language experts, and elementary school students. Data were collected through expert validation sheets, practicality questionnaires, and student learning outcome tests. Data analysis was conducted using descriptive quantitative and inferential statistics through a t-test. The results indicate that the developed textbook achieved a “very good” category in terms of feasibility based on expert evaluations and was considered highly practical by both teachers and students. The effectiveness test showed a significance value of 0.000 (p < 0.05), indicating that the use of BUDIPAS significantly improves students’ learning outcomes. Therefore, the CRT-based textbook is proven to be effective and has implications for fostering more meaningful, contextual, and responsive learning aligned with students’ characteristics.